Cost effectiveness of full coverage of the medical management of smoking cessation in France. Issue 3 (29th November 2012) - Chevreul, Karine; Cadier, Benjamin; Durand-Zaleski, Isabelle; Chan, Elis; Thomas, Daniel
Abstract : Objective: To estimate the incremental cost effectiveness of full coverage of the medical management of smoking cessation from the perspective of statutory health insurance (SHI) in France. Design and population: Cost-effectiveness analysis based on a Markov state-transition decision analytic model was used to compare full SHI coverage of smoking cessation and actual coverage based on an annual €50 lump sum per insured person among current French smokers aged 15–75 years. We used a scenario approach to take into account the many different behaviours of smokers and the likely variability of SHI policy choices in terms of participation rate and number and frequency of attempts covered. Interventions: Drug treatments for smoking cessation combined with six medical consultations including individual counselling. Main outcomes measures: The cost effectiveness of full coverage was expressed by the incremental cost-effectiveness ratio (ICER) in 2009 euros per life-year gained (LYG) at the lifetime horizon. Results: The cost effectiveness per LYG for smokers ranged from €1786 to €2012, with an average value of €1911. The minimum value was very close to the maximum value with a difference of only €226. The cost-effectiveness ratio was only minimally sensitive to the participation rate, the number of attempts covered and the cessation rate. Conclusions: Compared to other health measures in primary and secondary prevention of cardiovascular disease already covered by SHI, full coverage of smoking cessation is the most cost-effective approach.